Perception of formal and informal institutions by entrepreneurs in China, Morocco, and Germany: A cross-cultural pilot study - Rainer Busch; Karim Gassemi; Julie Papastamatelou; Alexander Unger; Christian May (International Journal of Management and Economics, 2020)
Introduction and Aims Entrepreneurship and the business environment, in general, are being influenced by the existence of formal and informal institutions. This study focuses on the negative versus positive perceptions of Moroccan, Chinese, and German entrepreneurs to formal and informal institutions, and the associations of these perceptions with self-efficacy and market versus network orientation of the business environment. Methods In a sample of n = 319 female and male entrepreneurs, we have examined similarities and differences in the perception of informal and formal institutions and their effects on self-efficacy and business strategy, while conducting t-tests and linear regressions. Results In all three cultural contexts, both formal and informal institutions play a significant role because of different reasons. Conclusion The nature of entrepreneurship is complex as both formal and informal institutional factors are differently associated with businesses. The results could enhance the understanding regarding the coexistence of formal or informal institutions within the business environments of different countries and the connections between business orientation and self-efficacy.
Keywords: D02; D23; 650; formal institutions; informal institutions; self-efficacy; network orientation; market orientation